Pengaruh komitmen kerja dan lingkungan kerja terhadap kinerja karyawan PT Cemerlang Tunggal Intikarsa Jakarta Barat - Ramadhani , Juwita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to prove whether there is a partial effect of Work Commitment and Work Environment on Performance. In addition, it is also to find out how much influence the Work Commitment and Work Environment have simultaneously on the Employee Performance of PT Cemerlang Tunggal Intikarsa, West Jakarta. This study uses quantitative methods. The population used in this study were all 80 employees of PT Cemerlang Tunggal Intikarsa, West Jakarta. Data analysis using regression method. Based on the results of this study indicate that there is a significant effect simultaneously (together) between Work Commitment (X1) and Work Environment (X2) on Performance (Y). The results of partial correlation coefficient analysis between Work Commitment to Performance obtained a correlation coefficient value of 0.577 meaning that the two variables have a moderate level of relationship, the results of partial correlation coefficient analysis between Work environment and Performance obtained a correlation coefficient value of 0.607 meaning that the two variables have a high level of relationship. strong, and based on the results of the simultaneous correlation coefficient between Work Commitment and Work Environment on Performance, the correlation coefficient value of 0.662 means it has a strong relationship. and H3 is rejected. Based on the results of the F test, it was found that Work Commitment had an effect and Work Environment had an effect on Employee Performance.